Utilising common bean and strawberry vegetative wastes in yellow mealworm (Tenebrio molitor) substrates: effects of pre-treatment on growth and composition - Wael Yakti; Simon Schulz; Nadja Förster; David Deruytter; Marcus Müller; Inga Mewis; Christian Ulrichs (Scientific Reports)
Abstract Integrating plant production with insect farming, termed "entomoponics," involves using plant waste as a substrate for insect rearing, while returning insect frass to fertilise the plants. In this study, vegetative wastes from strawberry (Fragaria x ananassa), and common bean (Phaseolus vulgaris), were incorporated into a wheat bran-based substrate for rearing the yellow mealworms (MW; Tenebrio molitor). The wastes were either autoclaved or autoclaved then fermented with the fungus Trichoderma reesei, and mixed in a 50:50 ratio with wheat bran. Replacing 50% of the wheat bran with autoclaved beans waste did not significantly affect MW yield, but the yield was reduced when beans wastes were fermented or left untreated. Incorporating beans waste, whether treated or untreated, increased the Ca, K, and Fe content in the MW. Incorporating strawberry vegetative waste into the substrate compensated the yield regardless of the pre-treatment, but enhanced Mn, Zn, and Fe levels in the produced MW. Plant flavonoids were reduced when the wastes were pre-treated and did not accumulate in the MW biomass. These findings provide insights into using plant vegetative wastes as a partial supplement in MW rearing substrates, and the potential effects on the growth and nutritional composition of the resulting MW biomass.